CLASSIFICATION OF LOGISTICS-BASED TRANSPORTATION ACTIVITIES IN OECD COUNTRIES AND SELECTED NON-MEMBER COUNTRIES THROUGH CLUSTER ANALYSIS - KÜMELEME ANALİZİ İLE OECD ÜLKELERİ VE SEÇİLMİŞ ÜYE OLMAYAN ÜLKELERİN LOJİSTİK FAALİYETLERİNE DAYALI TAŞIMACILIK SINIFLANDIRILMASI - Gülsen Serap Çekerol (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Logistics involves not only transportation of products, but also all the procedures that make it possible to deliver products to customers without any problems starting from production phase. Transport is the basic component of logistics, which is a process-based activity. This study aims to classify 47 countries according to the statistics about OECD (Organization for Economic Cooperation and Development) countries and selected non-member countries through hierarchical clustering and fuzzy clustering in terms of transportation activity indicators, which play an important role in countries' economic development. The study found that there are clusters in which the countries available in OECD statistics are similar or different in terms of transport indicators. The cluster which Turkey belongs to was also presented within the scope of the study.